How to prevent destruction: on the malleability of anti-social behavior - Müller, Julia; Schwieren, Christiane; Spitzer, Florian (Journal of behavioral and experimental economics, 2022)
Experimental evidence for anti-social preferences has been identified in studies employing economic destruction games; in these games, some subjects destroy other subjects’ incomes without receiving any material benefit, and they may even incur costs in doing so. Here, we study the robustness of this phenomenon. We introduce a four-player destruction game in which we vary the way the game is framed and the presence of an alternative task that is performed in parallel to the destruction game. In the baseline condition, where the game is framed in the spirit of previous destruction experiments and when no parallel activity is present, we observe a substantial amount of destruction. Our results indicate that including a parallel activity and framing the game to emphasize joint ownership of the item to be destroyed reduces destruction to almost zero. We conclude that the emergence of anti-social behavior can be prevented by appropriately changing the institutional environment.
Available online 19 November 2021
Gesehen am 20.05.2022